Datko criteria for uniform instability in Banach spaces - BORUGA (TOMA), Rovana; MEGAN, Mihail (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The main objective of this paper is to present some necessary and sufficient conditions of Datko type for the uniform exponential and uniform poly- nomial instability concepts for evolution operators in Banach spaces. Mathematics Subject Classification (2010): 47D06, 47B01.